Termination of SNAP Emergency Allotments, Food Sufficiency, and Economic Hardships - Dasgupta, Kabir; Plum, Alexander (Board of Governors of the Federal Reserve System, 2023)
To meet the rising need for food and nutrition assistance during the pandemic in the United States, all states were approved to provide Emergency Allotments (EA) to households enrolled in the Supplemental Nutrition Assistance Program (SNAP). In this analysis, we use the Census Bureau’s Household Pulse Surveys and exploit staggered state-level variation in dissolution of the SNAP EA payments to study whether the end of EA is associated with food-related challenges and economic hardships. Our findings indicate that EA termination is followed by a decrease in the likelihood that adult survey respondents had sufficient food for consumption and an increase in the probability of experiencing difficulty in paying meeting with usual household expenses. These findings provide policy-relevant insights into the potential impact of the nationwide termination of the EA payments that came into effect in early 2023.
Keywords: 38 Economics; 3801 Applied Economics; Nutrition; 2 Zero Hunger